Sodium Acetate Buffer - Chohan, I. S; Vermylen, J; Singh, I; Balakrishkan, K; Verstraete, M (Thrombosis and Haemostasis, 1975)
Sodium acetate buffer, 0.12 M, pH 7.4 as a diluent in the low temperature technique of dilute clot lysis time, is more effective in accelerating the velocity of lysis than phosphate buffer of similar pH and molarity. A uniform shape of the clot is maintained throughout the digestion in sodium acetate buffer and the end point of lysis is characteristically marked by an abrupt and sharply defined disintegration. Sodium acetate buffer can be employed advantageously in this technique not only to improve the observation but also to shorten the lysis times.